Buy versus build: Navigating Artificial Intelligence (AI) tool adoption in academic libraries - Michalak, Russell; Ellixson, Devon (Information services & use, 2024)
This paper explores the strategic decision to buy (vs build) Artificial Intelligence (AI) tools for use in higher education and academic libraries. It discusses the benefits and challenges associated with this approach and provides insights that can guide other academic libraries in making informed decisions about AI-driven tool adoption to support undergraduate research workflows. Detailed examples are provided and the pros/cons of each approach are provided.